z=ln(x+e^(-y))
dz/dx=1/(x+e^(-y))*(x+e^(-y))'=1/(x+e^(-y))
d2z/dx2=((x+e^(-y))^(-1))'=-(x+e^(-y))^(-2)*(x+e^(-y))'=-1/(x+e^(-y))^2
d3z/dx2dy=(-(x+e^(-y))^(-2))'=-(-2(x+e^(-y)))^(-3)*(x+e^(-y))'=2(x+e^(-y))^(-3)*(-e^(-y))=-2e^(-y)/(x+e^(-y))^3
dz/dy=1/(x+e^(-y))*(x+e^(-y))'=1/(x+e^(-y))*(-e^(-y))=-e^(-y)/(x+e^(-y))
d2z/dydx=(-e^(-y)*(x+e^(-y))^(-1))'=-e^(-y)*((x+e^(-y))^(-1))'=
-e^(-y)*(-((x+e^(-y))^(-2)))*(x+e^(-y))'=e^(-y)/(x+e^(-y))^2
d3z/dydx2=(e^(-y)/(x+e^(-y))^2)'=e^(-y)((x+e^(-y))^(-2))'=
e^(-y)*(-2((x+e^(-y))^(-3)))*(x+e^(-y))'=-2e^(-y)/(x+e^(-y))^3
и все
-2e^(-y)/(x+e^(-y))^3-(-2e^(-y)/(x+e^(-y))^3)=-2e^(-y)/(x+e^(-y))^3+2e^(-y)/(x+e^(-y))^3=0
Объяснение:
35
Объяснение:
f(х) = х²+4, g(х)= 2х +1
f(1)•g( 3)=?
f(1) = 1²+4=1+4=5
g(3)=2*3+1=6+1=7
f(1)•g( 3)=5*7=35